(untitled) (Circe de clásicos y modernos, 2018)
Our objective is twofold: 1) to point out the convenience of incorporating some possible neologisms or other words found in Aquinas’ Commentary on John in future editions of lexicons or in new works devoted to Medieval Latin; 2) to reflect on the problems that a nonspecialist reader may face when consulting the common Latin dictionaries.